Między nerdem a zawodnikiem - autokreacja wizerunku e-sportowców w mediach społecznościowych na przykładzie Facebooka = Between a nerd and a player - self-creation of thee-sports players` social media image based on the example of Facebook - Kinal, Artur (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper addresses the issue of the duality of associations evoked by e-sports. On the one hand, its prefix evokes computer and Internet connotations; on the other hand, the root of the word refers to an activity traditionally associated with movement and physical exercise. The gap between these two opposites contributes to the controversy surrounding e-sports. The aim of the article is to find out how leading Polish e-sports players cope with the issue of the above duality. The author seeks to answer this question by analysing the self-creation of the image of e-sports players in social media. Selected profiles were studied by means of an analysis of visual and textual content.
Keywords: e-sport; socjologia wizualna; kreacja wizerunku; media społecznościowe; e-sports; visual sociology; image creation; social media